REPERTÓRIO COMPORTAMENTAL DE Aegla okora (Páez & Teixeira, 2018) (Crustacea, Decapoda, Aeglidae) EM CONDIÇÕES LABORATORIAIS - FERREIRA, BRUNA CAROLINE LOPES (2022)
The anomurans of the Aeglidae family are represented by a single genus, Aegla Leach, 1820, consisting of 85 species with geographic distribution restricted to the south of South America. In Brazil, there are 54 species, one of which, Aegla okora, described in 2018, is possibly endemic to the Center-South region of Paraná State, since it has only been recorded, in the Tapera River, a tributary of the Pinhão River, municipality of Pinhão, PR. Little is known about this new species and behavioral studies are important in understanding the life history of a species. In this sense, this work presents the behavioral repertoire exhibited by Aegla okora under laboratory conditions. The descriptions were carried out by the focal animal method, using 30 males and 30 females. For this, 15 couples were filmed for 18 minutes during the day and another 15 were filmed for 18 minutes during the night. Five behavioral classes were identified under laboratory conditions: Immobility (53.87%); Exploration of the environment (34.38%); Feeding (5.59%); Self-cleaning (4.84%) and Social interaction (1.40%). No reproductive behaviors were observed. All categories were displayed both at night and during the day. It can be said that crabs are more active at night, staying still longer, cleaning and burying themselves during the day and walking and swimming during the night. This fact may be related to a defense strategy against diurnal predators.